New Properties of Anti Fuzzy Ideals of Regular Semigroups - Asaad, Samah H.; Mohammed, Akram S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this article, we study some properties of anti-fuzzy sub-semigroup, anti fuzzy left (right, two sided) ideal, anti fuzzy ideal, anti fuzzy generalized bi-ideal, anti fuzzy interior ideals and anti fuzzy two sided ideal of regular semigroup. Also, we characterized regular LA-semigroup in terms of their anti fuzzy ideal.